The Role of Internal Control System in Health Services - Meiryani,; Juwita, Anita; Natawidjaja, Melia Asmita; Fitri, Yessi (International Journal of Psychosocial Rehabilitation, 2020)
The author conducts research with case studies at the Royal Taruma Hospital in Jakarta, Indonesia. The population in this study were all employees at the Royal Taruma Hospital. The author uses a purposive sampling method to determine respondents at the Royal Taruma Hospital. Respondents are employees who work in the department of internal control systems and accounting and finance. This study aims to find out how the implementation of the implementation of internal control systems in Loyal Taruma Hospital. This research is a descriptive qualitative research using primary data and secondary data obtained through interviews, observation, and documentation with related documents and parties concerned with internal control systems at Royal Taruma Hospital. The results of this study indicate that the internal controls implemented in Royal Taruma Hospital have been running well.